Beneficial effects of Alterion supplementation on growth metrics, intestinal histomorphology, and microbial communities in indigenous and commercial chicken breeds - Al-Marzooqi, Waleed; Elaswad, Ahmed; El-Zaiat, Hani M.; ElTahir, Yasmin; Al-Kharousi, Kaadhia; Hassan, Syed K. (Frontiers in Veterinary Science, 2025)
This study evaluated the effects of Alterion supplementation on growth rate, feed conversion ratio, intestine morphology, carcass quality, and blood indices in both commercial and local chicken breeds. Two chicken breeds (Local Omani and Cobb 430 broilers) and two dietary treatments (Control and 0.05% Alterion) were used in a 2 × 2 factorial design. The results showed that, across both breeds, supplementation significantly improved weight gain over 42 days compared to the control. Specifically, the Alterion group exhibited a 12.1% increase in Cobb 430 and a 26.7% increase in Omani birds, with all differences being statistically significant (p < 0.001). Furthermore, the jejunum and ileum of both breeds fed supplemented diets exhibited higher villus height and villus-to-crypt ratio than the control group (p < 0.05). The counts of red blood cells (RBCs), white blood cells (WBCs), and total protein increased significantly in both chicken breeds fed supplemented diets compared with controls (p < 0.05). Carcass and internal organs were remarkably larger in Cobb 430 than in Omani chickens (p < 0.05), and in Alterion treatments than in controls (p < 0.05). In both chicken breeds, meat quality parameters were not significantly affected by Alterion. Alterion supplementation modulated gut microflora composition and relative abundance, with Bacilli being the most abundant class in all treatments and gut segments (p < 0.05). While Alterion supplementation had minimal influence on the overall composition of the bacterial community, it contributed to maintaining a normal ecological balance of the microbiota. In summary, supplementation with 0.05% Alterion improved growth, intestinal health, blood parameters, carcass yield, and internal organ weight, and beneficially modulated the gut microbiome in Cobb 430 and Omani chickens. Further research is recommended to determine the optimal dosage of Alterion for Omani chickens, thereby optimizing their performance.